2012
DOI: 10.1524/stuf.2012.0010
|View full text |Cite
|
Sign up to set email alerts
|

Stress-timed = word-based? Testing a hypothesis in prosodic typology

Abstract: Stress-timed = word-based? Testing a hypothesis in prosodic typology AbstractIn recent research on cross-linguistic differences in linguistic rhythm, it has been hypothesized that the traditional dichotomy 'stress-timed' versus 'syllable-timed' might be recast with respect to which level of the Prosodic Hierarchy constitutes the most prominent domain for the organization of prosodic structure. In this paper, we test the prediction that 'stress-timed' languages are characterized by a dominance of the prosodic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Lest the reader think that recent work has closed the case on any notion of wordhood, I end this review by pointing out some of the empirical, methodological, and conceptual problems of the studies that are critical of the notion of the word reviewed above. The typological research on phonological wordhood domains conducted by Bickel, Hildebrandt, and Schiering () and Schiering and Bickel () did not focus on morphophonological processes above the word (e.g., phonological phrase) . It is possible that inclusion of higher‐level phonological processes may have revealed more significant clustering in patterns.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Lest the reader think that recent work has closed the case on any notion of wordhood, I end this review by pointing out some of the empirical, methodological, and conceptual problems of the studies that are critical of the notion of the word reviewed above. The typological research on phonological wordhood domains conducted by Bickel, Hildebrandt, and Schiering () and Schiering and Bickel () did not focus on morphophonological processes above the word (e.g., phonological phrase) . It is possible that inclusion of higher‐level phonological processes may have revealed more significant clustering in patterns.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…An obvious candidate in the case of Limbu would be stress. However, Schiering and Bickel () show that there is no typological evidence that stress domains correlate with other domains beyond chance. The only generalization is that stress domains tend to be larger than other phonological domains.…”
Section: The Phonological Wordmentioning
confidence: 99%
“…using standard statistical tools of data-mining such as multidimensional scaling, what if any patterns there are in the distribution of prosodic domains across languages. In Bickel, Hildebrandt & Schiering 2009, we test whether there are probabilistic clusters of similarly-sized domains relative to the kind of sound pattern involved, e.g. tonal vs. segmental processes.…”
Section: The Prosodic Word As An Emergent Categorymentioning
confidence: 99%
“…We already used the related measure of ‘word dominance’, i.e. the frequency of reference to the most frequently referenced domain, to test whether languages formerly classified as ‘stress-timed’ indeed show more evidence for prosodic words than languages of other rhythm classes as hypothesized by Auer 1993 (Schiering 2009). It turns out that there is a trend for stress-timed languages in Indo-European and Sino-Tibetan to have more patterns reference their most frequent domains than syllable- or mora-timed languages.…”
Section: The Prosodic Word As An Emergent Categorymentioning
confidence: 99%
“…Typological studies on the validity of these claims lead to rather negative results (Schiering, 2007;Schiering et al, 2012). Schiering (2007) found that three logically independent aspects serve to characterize the rhythm of a language: the salience of stress phonology in the language, syllable complexity and the relevance of length contrasts typical of mora-timing languages.…”
Section: Concepts Of Rhythmmentioning
confidence: 99%